2020
DOI: 10.1186/s40168-020-00918-6
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions as determinants of the arbuscular mycorrhizal fungal community with cascading plant-promoting consequences

Abstract: Background The soil mycobiome is composed of a complex and diverse fungal community, which includes functionally diverse species ranging from plant pathogens to mutualists. Among the latter are arbuscular mycorrhizal fungi (AMF) that provide phosphorous (P) to plants. While plant hosts and abiotic parameters are known to structure AMF communities, it remains largely unknown how higher trophic level organisms, including protists and nematodes, affect AMF abundance and community composition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…It should be further considered that G-bacteria contribute most likely only 10% to the total microbial biomass (Joergensen and Wichern 2008;Murugan et al 2021), i.e., markedly less than AMF (Faust et al 2017). For this reason, the neutral lipid fatty acid (NLFA) 16:1ω5 has sometimes been used as an AMF indicator (Jiang et al 2020) although NLFA do not solely occur in the biomass of organisms (Zelles 1999). Faust et al (2017) showed that PLFA 16:1ω5 and NLFA 16:1ω5 give similar information on the presence of AMF in soil and recommended solely using the PLFA as an indicator for AMF biomass.…”
Section: Correct Assignationmentioning
confidence: 99%
“…It should be further considered that G-bacteria contribute most likely only 10% to the total microbial biomass (Joergensen and Wichern 2008;Murugan et al 2021), i.e., markedly less than AMF (Faust et al 2017). For this reason, the neutral lipid fatty acid (NLFA) 16:1ω5 has sometimes been used as an AMF indicator (Jiang et al 2020) although NLFA do not solely occur in the biomass of organisms (Zelles 1999). Faust et al (2017) showed that PLFA 16:1ω5 and NLFA 16:1ω5 give similar information on the presence of AMF in soil and recommended solely using the PLFA as an indicator for AMF biomass.…”
Section: Correct Assignationmentioning
confidence: 99%
“…The high organic carbon content in organic amendments can promote the mycelial proliferation of AM fungi ( Hart and Reader, 2002 ), thus increasing the inoculation capacity of AM fungi on plant roots. Therefore, some studies found that colonization activity ( Qin et al, 2015 ; Jiang Y. J. et al, 2020 ) and AM fungal diversity ( Bhadalung et al, 2005 ; Lin et al, 2012 ) were higher on organic farms than on conventional farms. However, we hypothesize that these effects of conventional and organic farming systems on soil AM fungi may be different in low-quality farmlands for the following reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Structural equation modelling approach has been widely used to decipher keystone indicators associated with soil function and crop production in agroecosystems (Jiang et al, 2020;Chen et al, 2019).…”
Section: Fig 6 Here 4 Discussionmentioning
confidence: 99%